(untitled) (American Journal of Islam and Society, 2006)
Gianotti’s purpose behind this monograph is to draw out Ghazali’s position on the vexed question of the true nature of the soul and its state in the afterlife. Ghazali’s actual views on this question have been a point of serious debate in both the Muslim intellectual tradition and Ghazali scholarship in the West. At the heart of this debate lies the question of his true allegiance: Was the man, widely held to be the mujaddid (renewer of religion) of the fifth Islamic century, a full-fledged Asharite, as tradition has made him out to be, or was he, as others have suggested, a closet Avicennian? Or was he, to complicate matters even further, neither? The source of the problem rests on the apparently conflicting doctrines he articulated in various places concerning the soul in various places in his vast and multi-layered literary oeuvre. These seeming inconsistencies led Averroes, in the thirteenth century, to accuse Ghazali of adhering “to no one doctrine in his books,” and of being a Sufi with Sufis, an Asharite theologian with the Asharites, and a philosopher with the philosophers (p. 19). Gianotti confesses that the “tensions and ambiguities are real and beg resolution” (p. 8). He poignantly asks, however, whether they were the “unintentional mess left by a brilliant but indisciplined mind,” or whether ...